PEMODELAN ANGKA MORTALITAS IBU DI PROVINSI BALI MENGGUNAKAN METODE REGRESI POISSON - AGUSVIANI, NI PUTU NADYA; SUKARSA, I KOMANG GDE; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 11 No 1 (2022), 2022)
Maternal Mortality Rate (MMR) is a metric used to assess a region's maternal health status. Maternal death occurs when a woman dies during pregnancy or until 42 days after to the pregnancy itself or its handling. It does not count if the death occurred as a result of an accident or injury. There are number of factors that cause maternal death, one of which is the direct factor that still dominates up to now on. In this study, MMR modeling in Bali was conducted in 2019 by using 6 factors that are thought to be influential. Poisson Regression method is used to determine the factor that cause maternal death. Based on this study of maternal death rate in Province of Bali, it shows that the percentage of pregnant mother visits K1 (X 1 ) and the percentage of obstetric complication cases (X 2 ) are significant towards the variable.